A study on the perception of islamic banks among teenagers without islamic studies background / Nabila Mohamed Nazim - Mohamed Nazim, Nabila (Faculty of Business and Management, 2019)
Islamic banking is a banking system based on Shariah law. International Association of Islamic Banks (IAOIB) define Islamic banking as a banking system which is established in accordance to Islamic Shariah principle with the objective to improve the Islamic financing system and to help both Muslims and non-Muslims. Islamic banking has grown over the years due to its strict lending principles and it is less risky alternatives for investment. However, there are misconception and sceptical views about doing banking in Islamic way because of limited knowledge among customers regardless of their religion. The limited knowledge regarding Islamic banking and finance industry has affected the usage of Islamic banking facilities among customers. Based on a previous study conducted by Chowdury (2013), they find out that most of the respondents does not have enough knowledge about Islamic banking. Moreover, majority of the respondents even thought that Islamic banking and finance is just another way to attract customers. Therefore, an additional research is necessary to be conducted by focusing on the teenagers that does not have any Islamic background studies. Based on result of this study, we found that teenagers without Islamic studies background perceived confidence in Islamic banking as significant variable